Stem Cell Biology in Normal Life and Diseases - Alimoghaddam, Kamran (IntechOpen, 2013)
Stem cells have a prominent role in normal life and also in pathogenesis of disorders. Today, these cells are clinically applicable in hematopoietic stem cell transplantation but expansion of their application in many more disorders needs more work. For safe and effective application of these cells, we need better knowledge of their biology, their interaction with other cells (especially supporting niche cells), growth, maturation and also immigration of stem cells through body in normal and abnormal conditions. Also for clinical application we need to understand better, their separation methods and safe manipulation. This book is written to clarify some aspects of stem cell biology, their characteristics, assessment of damage to cells during ex vivo manipulation and also their role in a model of cancers (chronic myeloid leukemia).